The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.18052/www.scipress.com/ilcpa.24.17
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heat Treatment on the Electrochemical Properties and Corrosion of Aluminium Alloy AA8011 in an Aqueous Acid Media

Abstract: Effects of heat treatment and quenching regimen on the electrochemical corrosion behaviour of aluminium alloy AA8011 in 0.1M H 2 SO 4 was studied by open circuit potential, potentiodynamic polarization and electrochemical impedance spectroscopy measurements. Three different specimens (untreated/ control, air -quenched oven-quenched) were investigated. Polarization results show that all the specimens underwent active dissolution, with no distinctive transition to passivation, heat treatment was observed to shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Such behavior has been reported in other publications as well . Double-layer capacitance decreases following Se addition to Ru/C, which indicates an increase in charge-transfer resistance for both hydride and oxide formation originating from Ru and Se interactions . In Ru/C, an anodic current corresponding to Ru–OH formation and a cathodic current corresponding to the reduction of Ru–OH can be detected.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Such behavior has been reported in other publications as well . Double-layer capacitance decreases following Se addition to Ru/C, which indicates an increase in charge-transfer resistance for both hydride and oxide formation originating from Ru and Se interactions . In Ru/C, an anodic current corresponding to Ru–OH formation and a cathodic current corresponding to the reduction of Ru–OH can be detected.…”
Section: Resultssupporting
confidence: 85%
“…However, after heat treatment, there is a single anodic peak at 0.90 V vs RHE corresponding to Se oxidation, thus indicating stabilization of the Ru/C moiety. This observed increase in stability of heat treated RuSe/C is due to an improved alloy formation between the metals, thereby preventing the formation of Se and Ru oxides. , The CV of RuSeMo/C had similar features as that for RuSe/C, and is shown in the Supporting Information, Figure S1.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Table 3: Corrosion potential and polarization resistance of the aluminum packaging foil for cheese in the presence and absence of the magnetic field for a sample area of 1 cm 2 in a 0.3 % of mass fractions of NaCl medium Tabela 3: Korozijski potencial in polarizacijska upornost aluminijeve embala`ne folije za sir ob prisotnosti in odsotnosti magnetnega polja za vzorec s povr{ino 1 cm 2 Other authors observed the presence of the AlSiFe, AlFe, AlFeMn, and AlSi phases in alloys with the compositions similar to the alloys presented in this study. [17][18][19] Okeoma Kelechukwu et al 18 observed the AlFeMn and MnFe particles in the AA8011 aluminum alloy containing 0.1 % of Mn used as a packaging foil. They noticed that the presence of the Fe and Si elements in the material support the precipitation of the dispersoids and decreases the solubility of Mn in a solid solution.…”
Section: Corrosion Morphology Of Aluminum Packaging Foilmentioning
confidence: 99%
“…8006 aluminium alloys are mostly preferred by foil and sheet aluminium manufacturers for food packaging applications (Kurt et al, 2013;Kelechukwu et al, 2014;Rahimi et al, 2015). The twin-roll casting method is ideal for the production of foil aluminium because of cost-effectiveness and fewer production stages.…”
Section: Introductionmentioning
confidence: 99%